2009
DOI: 10.1002/biot.200900004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cell viability during bioprinting processes

Abstract: Bioprinting is an emerging technology in the field of tissue engineering and regenerative medicine. The process consists of simultaneous deposition of cells, biomaterial and/or growth factors under pressure through a micro-scale nozzle. Cell viability can be controlled by varying the parameters like pressure and nozzle diameter. The process itself can be a very useful tool for evaluating an in vitro cell injury model. It is essential to understand the cell responses to process-induced mechanical disturbances b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
320
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(346 citation statements)
references
References 34 publications
16
320
1
2
Order By: Relevance
“…Several works showed that stresses transmitted to the cells are a function of the dispensing nozzle characteristics (geometry, diameter and length), applied pressure, deposition speed, and bioink rheological properties. These studies also demonstrated the possibility to determine and to reduce the shear stresses transmitted to the cells through experimental and numerical studies [17,19,30,46,127]. To address the unique requirements of extrusion bioprinting regarding the print fidelity and biological characteristics, research efforts have been focused on the development of bioinks exhibiting appropriate rheological, mechanical and biological properties [28,32,74,82,100,152,169,174].…”
Section: Extrusion Bioprintingmentioning
confidence: 99%
“…Several works showed that stresses transmitted to the cells are a function of the dispensing nozzle characteristics (geometry, diameter and length), applied pressure, deposition speed, and bioink rheological properties. These studies also demonstrated the possibility to determine and to reduce the shear stresses transmitted to the cells through experimental and numerical studies [17,19,30,46,127]. To address the unique requirements of extrusion bioprinting regarding the print fidelity and biological characteristics, research efforts have been focused on the development of bioinks exhibiting appropriate rheological, mechanical and biological properties [28,32,74,82,100,152,169,174].…”
Section: Extrusion Bioprintingmentioning
confidence: 99%
“…Viscosity is defined by the concentration of the materials, and the printability and print resolution can be enhanced as the viscosity of the bioink increases. However, it is reported that cell viability can decrease from the severe nozzle wall shear stress generated in a narrow nozzle by high pressure, and this is required to print high-viscosity bioink [63] . In addition, it is known that the ability to crosslink effects the strength and stiffness of the scaffolds and the oxygen and nutrient supply for the cells.…”
Section: Bioink Viscosity and Crosslink Abilitymentioning
confidence: 99%
“…[53][54][55] The applications of inkjet technology to tissue printing have been rapidly advanced in past few years; however the usage of inkjet tissue printing technique is hampered by some limitations including the size of the jetting needle, the cell concentration, the viscosity of the material and the viability of the printed cells. 56,57 Although inkjet tissue printing has faced some shortcomings, there are some other jet-based techniques which can overcome disadvantages of the inkjet printing.…”
Section: Directed Assembly Of Cell-laden Hydrogels For Engineering Timentioning
confidence: 99%
“…Tissue printing is an attractive scaffold free technique with the great potential of constructing delicate 3D tissue-like structures. [51][52][53][54][55][56][57][58][59][60][61] (Fig. 6A-F).…”
Section: Directed Assembly Of Cell-laden Hydrogels For Engineering Timentioning
confidence: 99%